Hubungan Status Sosial Ekonomi Orang Tua dengan Minat Belajar pada Siswa Di MTSs Darul Hasanah Tahun Pembelajaran 2021/2022 - Bea Johana; Dina Hidayati Hts (Journal on Education, 2023)
This study aims to determine the relationship between parents' socioeconomic status and interest in learning in class VII MTSS Darul Hasanah. The hypothesis proposed is that there is a positive and significant relationship between the socio-economic status of parents and learning interest in students in class VII MTSS Darul Hasanah. The research method used is a quantitative descriptive approach with the type of research used is correlational descriptive research. Determination of the research sample is population research because the sample is less than 100. The population in this study is 82 people to obtain the necessary data, so in this study researchers used data collection tools in the form of questionnaires and documentation. Based on the results of research at MTsS Darul Hasanah using the calculation of the product moment correlation of the two variables Learning Interest (X) and the Relationship of Parents' Socio-Economic Status (Y). the level of student interest in learning was 96.93% in the high category, the level of socio-economic status of parents was 83.57% in the high category, the level of relationship between socio-economic status of parents and interest in learning was ????ℎi????????????g 0.331> ???????????????????????? 0.284. This shows that there is a relationship between the socio-economic status of parents and students' interest in learning. This study aims to determine the relationship between parents' socioeconomic status and interest in learning in class VII MTSS Darul Hasanah. The hypothesis proposed is that there is a positive and significant relationship between the socio-economic status of parents and learning interest in students in class VII MTSS Darul Hasanah. The research method used is a quantitative descriptive approach with the type of research used is correlational descriptive research. Determination of the research sample is population research because the sample is less than 100. The population in this study is 82 people to obtain the necessary data, so in this study researchers used data collection tools in the form of questionnaires and documentation. Based on the results of research at MTsS Darul Hasanah using the calculation of the product moment correlation of the two variables Learning Interest (X) and the Relationship of Parents' Socio-Economic Status (Y). the level of student interest in learning was 96.93% in the high category, the level of socio-economic status of parents was 83.57% in the high category, the level of relationship between socio-economic status of parents and interest in learning was ????ℎi????????????g 0.331> ???????????????????????? 0.284. This shows that there is a relationship between the socio-economic status of parents and students' interest in learning.